The noble art of abbreviating - Lehmann, Henning (Proceedings of the Danish Institute at Athens, 1995)
Originally, this paper was intended to have as its modest subtitle the words: “Some simple remarks’’, for, what will be presented, will not be anything like either a broad or a thorough analysis of rhetoric practice or principle in Antiquity in abbreviating procedures. What I shall try to do is - in a very simple, straightforward and elementary way - to look at a few instances where texts attributed to Severian of Gabala appear in more than one version, usually in what may be considered a “full-length” version and some kind of abbreviated form. On my way through the examples I considered more than once the possibility of transferring the adjective “simple” from the subtitle to the main title, having ascertained that the procedure of abbreviating very often is quite a simple one. So the art of abbreviating is, maybe, not always a noble one; on the other hand, the abbreviated form o f a text often has a particular strength of expression, entirely its own, so I left the notion of “noble” in the title; but I certainly ask and warn my readers to retain the notion of “simple” as a subtitle for what follows.